Health generating community assets University polyclinic 19 de April: Activos comunitarios generadores de salud del Policlínico Universitario 19 de Abril - Dandicourt-Thomas, Caridad (2022)
Introduction: Community assets are resources present within a community that, through the integration of different sectors and the active participation of all members, promote a model focused on identifying and strengthening community opportunities and capacities. Objectives: To develop a map of community assets within the community served by the “19 de Abril” University Polyclinic that contribute to health generation. Methods: The study was based on methodologies validated in previous research for the development of health asset mapping. Discussion workshops were conducted to actively identify individuals and groups within the community engaged in activities that could generate health. In addition, key informants, social actors, and formal community leaders were consulted to determine which of the ongoing activities in the community were considered health assets or resources. Results: Through workshops, interviews with key informants, social actors, and formal community leaders, 24 community assets contributing to the health of the served population were identified. These identified assets were plotted on a community map. Conclusions: The assessment conducted with the active participation of all stakeholders enabled the development of a map of community health assets located within the service area of the “19 de Abril” Polyclinic.